Using Pyridinium Styryl Dyes as the Standards of Time-Resolved Instrument Response. Issue 7 (July 2016) - Li, Lei; Chang, Mengfang; Yi, Hua; Jia, Menghui; Cao, Xiaodan; Zhou, Zhongneng; Zhang, Sanjun; Pan, Haifeng; Shih, Chun-Wei; Jimenez, Ralph; Xu, Jianhua
In this paper, two pyridinium styryl dyes, [2-(4-dimethylamino-phenyl)-vinyl]-1-methylpyridinium iodide (DASPMI), were synthesized and characterized by steady state fluorescence spectroscopy as well as picosecond and femtosecond time-resolved fluorescence spectroscopies. Both dyes exhibit large Stokes shifts and fluorescence decays equivalent to the instrument response function (IRF) standards employed in time-correlated single-photon counting. Due to their styryl and pyridinium moieties, DASPMIs have higher peak fluorescence intensity and shorter excited-state lifetimes than iodide ion-quenched fluorophores. The fluorescence lifetimes of o-DASPMI and p-DASPMI were measured to be 6.6 ps and 12.4 ps, respectively. The fluorescence transients of these DASPMIs were used as the IRFs for iterative reconvolution fitting of the time-resolved fluorescence decay profiles of Rhodamine B (RhB), sulforhodamine B (SRB), and the SRB-SRB2m RNA aptamer complex. The quality of the fits employing the DASPMI-derived IRFs are consistently equivalent to those employing IRFs obtained from light scattering. These results indicate that DASPMI-derived IRFs may be suited for a broad range of applications in time-resolved spectroscopy and fluorescence lifetime imaging microscopy (FLIM), especially in the visible emission range.